Rancang Bangun Sistem Informasi Perpustakaan Pada Madrasah Aliyah Negeri (MAN) Kaur - Wahid, Abdul; Khairil, Khairil; Zulfiandry, Ricky (Jurnal Media Infotama, 2025)
The development of education is inseparable from competition between schools to produce the best graduates. MAN Kaur is also striving to improve the quality of education by providing various facilities for students, especially libraries. This study aims to design and develop a web-based library information system at MAN Kaur. This system was developed to address issues in library management that are still done manually, such as recording loans, returns, and managing member data, which are prone to errors and data loss. The system development uses Waterfall method, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The main features built into the system include book data management, member data, borrowing and return transactions, as well as the automatic and structured generation of reports. Based on the implementation results, this information system is effective in improving operational efficiency and data management accuracy. Additionally, the system supports enhanced library service quality and serves as an appropriate solution for meeting digitalization needs within the school environment, particularly for MAN Kaur.